Perlindungan Hak Asasi Manusia dalam Penegakan Hukum: Studi Empiris terhadap Kasus Kriminalisasi Aktivis - Lukum, Abdul Fatah; Hukumu, Syahrul (Universitas Sains dan Teknologi Komputer, 2025)
The criminalization of activists in Indonesia remains a critical human rights issue, with legal regulations often used to suppress freedom of expression and civil liberties. Despite Indonesia’s commitment to human rights protection, repressive law enforcement practices indicate an imbalance between state interests and civil rights safeguards. This study analyzes how existing legal frameworks contribute to activist criminalization and assesses the effectiveness of legal protection mechanisms. Using a qualitative empirical approach, this study examines legal regulations, court rulings, and case studies of activist criminalization. Data were collected through interviews with activists, human rights lawyers, and legal scholars, supported by legal document analysis. Findings reveal that activist criminalization cases increased by 75% from 2018 to 2023, with 70% of targeted activists experiencing legal intimidation leading to job loss, psychological pressure, and social insecurity. Additionally, 90% of criminalized activists faced prolonged legal battles, with only 10% acquitted. Ambiguous legal provisions, particularly in the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP), are frequently misused to silence activism. This study highlights the urgent need for inclusive legal reform and stricter oversight mechanisms to prevent the misuse of laws against civil society. The findings provide a foundation for future research and policy recommendations to strengthen human rights protections and ensure that legal instruments are not exploited to suppress activism.